Fast and accurate transient simulation of magnetic gears - Alok Sahoo; V. S. S. Pavan Kumar Hari (AIP Advances, 2024)
Magnetic gears, being contactless, offer distinct advantages over mechanical gears. Transient simulations are required for the evaluation of dynamic performance, but the complex geometry of magnetic gears makes them computationally intensive with high simulation time. This paper proposes a method to perform a time-domain transient analysis on a coaxial magnetic gear. The proposed method is derived by an appropriate and timely modification of specific terms in the magnetostatic solution, to result in a computationally efficient transient simulation. The proposed method also doesn’t necessitate individual magnetostatic solutions for different time instances. The transient speed and torque performance of a coaxial magnetic gear can be predicted much faster with the proposed analytical approach (up-to 60 times faster for the configuration used in this article) compared to a finite element method (FEM)-based simulation. Accuracy of the proposed method is verified by comparing the results with those obtained from FEM simulations (COMSOL).